Mortality associated with the use of non‐vitamin K antagonist oral anticoagulants in cancer patients: Dabigatran versus rivaroxaban. (31st August 2021) - Lin, Yu‐Sheng; Kuan, Feng‐Che; Chao, Tze‐Fan; Wu, Michael; Chen, Shao‐Wei; Chen, Mien‐Cheng; Chung, Chang‐Ming; Chu, Pao‐Hsien; Lip, Gregory Y. H.; Wu, Victor Chien‐Chia
Abstract: Objective: This study assesses the mortality outcomes of non‐vitamin K antagonist oral anticoagulants (NOACs) in cancer patients with venous thromboembolism (VTE) and atrial fibrillation (AF). Methods: Medical records of cancer patients receiving NOACs for VTE or AF between January 1, 2011, and December 31, 2016, were retrieved from Taiwan's National Health Institute Research Database. NOACs were compared using the inverse probability of treatment weighting (IPTW) method. The primary outcome was cancer‐related death. Secondary outcomes were all‐cause mortality, major bleeding, and gastrointestinal (GI) bleeding. Results: Among 202, 754 patients who received anticoagulants, 3591 patients (dabigatran: 907; rivaroxaban: 2684) with active cancers were studied. Patients who received dabigatran were associated with lower risks of cancer‐related death at one year (HR = 0.71, 95% CI = 0.54–0.93) and at the end of follow‐ups (HR = 0.79, 95% CI = 0.64–0.98) compared with rivaroxaban. Patients who received dabigatran were also associated with lower risks of all‐cause mortality (HR = 0.81, 95% CI = 0.67–0.97), major bleeding (HR = 0.64, 95% CI = 0.47–0.88), and GI bleeding (HR = 0.57, 95% CI = 0.39–0.84) at the end of follow‐ups compared with rivaroxaban. Conclusion: Compared with rivaroxaban, the use of dabigatran may be associated with a lower risk of cancer‐related death and all‐cause mortality. Abstract : The outcomes of non‐vitamin K antagonist oral anticoagulants (NOACs) in cancer patients with venous thromboembolism (VTE) or atrial fibrillation (AF) are not known. A total of 3591 patients with active cancers were studied (907 on dabigatran; 2684 on rivaroxaban). In comparison with rivaroxaban, the use of dabigatran may be associated with lower risk of cancer‐related death and all‐cause mortality.